1989
DOI: 10.1101/gad.3.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sequence elements in the c-fos promoter mediate induction by cAMP.

Abstract: Induction of c-los by cyclic AMP in NIH-3T3 cells is distinct from induction by serum. Whereas induction by serum is mediated by the serum response element (SRE1, induction by cAMP does not require this element. In fact, no single sequence element in the c-fos promoter/enhancer is stringently required for the cAMP response. Rather, multiple sequence elements in the c-los promoter/enhancer can mediate induction by cAMP independently. These elements are: (1} the region from -72 to -54, which contains a binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
135
2
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(146 citation statements)
references
References 43 publications
(44 reference statements)
8
135
2
1
Order By: Relevance
“…The FAP1 site in the c-fos enhancer was previously found to mediate cAMP induction of reporter constructs redundantly with other elements in the cfos promoter such as the CRE site at 760 (Berkowitz et al, 1989;Fisch et al, 1989). However, the role of the FAP1 site in serum or growth factor induction has been less clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FAP1 site in the c-fos enhancer was previously found to mediate cAMP induction of reporter constructs redundantly with other elements in the cfos promoter such as the CRE site at 760 (Berkowitz et al, 1989;Fisch et al, 1989). However, the role of the FAP1 site in serum or growth factor induction has been less clear.…”
Section: Discussionmentioning
confidence: 99%
“…The CRE can mediate cAMP and calcium induction in certain cell types but may also contribute to growth factor induction (Berkowitz et al, 1989;Fisch et al, 1989;Sassone-Corsi et al, 1988;Sheng et al, 1990). The CRE is bound by CREB and the related transcription factor ATF1 (Ginty et al, 1994;Montminy, 1997;Sassone-Corsi et al, 1988).…”
mentioning
confidence: 99%
“…We chose the c-fos promoter because it is highly responsive to cAMP Berkowitz et al, 1989;Fisch et al, 1989; Metz and Zi, 1991) and because c-fos is ubiquitously expressed and unlikely to be dominantly repressed in MMSP cells. The c-fos promoter is also of signi®cance to MMSP because it is a possible target for EWS/ ATF1 (Brown et al, 1995) and is activated by a variety of mitogenic agents (Janknecht and Nordheim, 1996;Bannister et al, 1995;Nakajima et al, 1996;Ginty et al, 1994;Sheng et al, 1990;Dash et al, 1991;Bhattacharya et al, 1996).…”
Section: Activity Of the C-fos Promoter In Mmsp Cellsmentioning
confidence: 99%
“…Among those CRElike sequences, some have effects on basal or on cAMP-stimulated transcription or on both. These CRE-like motifs play either positive or negative roles in basal transcription (26,27) and display redundant roles in the response to cAMP (24,28). In the present study we have shown that dCRE, a motif conserved between rats, mice and humans, is a negative cis regulator of ACE gene basal expression.…”
Section: Discussionmentioning
confidence: 59%
“…CRE-like motifs in these promoters are usually multimers or single elements closely associated with other motifs and located in separated domains (24,25). Among those CRElike sequences, some have effects on basal or on cAMP-stimulated transcription or on both.…”
Section: Discussionmentioning
confidence: 99%